(untitled) (American Journal of Islam and Society, 2008)
Divided into five chapters plus a bibliography and an index, Arabic, Islam, and the Allah Lexicon explores Allah-centric expressions in Arabic and their far-reaching influence on the linguistic behavior of native Arabic speakers in particular and Muslims speaking their own languages in general. It clearly demonstrates how Islam’s advent constituted a turning point in the history of theArabic language by introducing numerous theocentric expressions reflecting God’s oneness, as opposed to the practice of polytheism in the pre-Islamic era. These expressions have successfully become the banner of day-to-day communication in Arab communities and, to a lesser extent, in non-ArabMuslim cultures. TheAllah lexicon inArabic has indeed shaped the concept of God inArab and/or Muslim culture; henceAllah’s omnipresence, omnipotence, and omniscience are linguistically felt in times of prosperity and adversity alike ...